TRANSLATIONAL CONSTRUCTION OF ISLAND IDENTITY IN AMERICAN NRMS’ TEXTS: POSTSTRUCTURALIST STUDY OF MALTA NARRATIVE IN AMERICAN ENGLISH AND KIRUNDI NWTS - Ntamwana, Simon; Adi, Ida Rochani; Adhitya, Galant Nanta (International Journal of Humanity Studies (IJHS), 2024)
The study investigated the construction of Island Identity through translation in American New Religious Movements’ texts (NRMs). The research used the descriptive qualitative method that is based on the American studies interdisciplinary method and Kristeva’s theory of intertextuality and notions of identity, abjection, and revolt. Moreover, Kovecses’ theory of Conceptual Metaphor (CM) in American Studies and Schmidt’s CM translation typology were used. Primary data were collected from the Kirundi New World Translation (NWT), American English NWT, and New American Standard Bible (NASB). Secondary data were obtained from books and articles about American NRMs, island, and CM translation. It was found out that in the conceptualization of alterity about island identity the source text (ST) is in abjection to the mainstream NASB. Moreover, the findings proved that, despite the subversion tints of the ascetic virtues from the center of the church, the target text (TT) is a nihilation of all island identity forms. Furthermore, it was discovered that the Burundi JW Bible imitates the ST to revolt against colonial and nationalist conceptualization and ipso facto to construct an island identity that supports the church’s propensity for the postnational and global discourse of American society and culture.